Graphene Protein Field Effect Biomedical Sensor for Glucose Measurements. Issue 1725 (23rd March 2015) - Liepmann, Dorian; Aran, Kiana; Ajayan, Pulickel M.; Viswanathan, Sowmya; Li, Pingzuo; Renugopalakrishnan, V.
ABSTRACT: The need for improved medical sensors based on lab-on-a-chip technologies has increased significantly because of the dramatic growth in the number of people with chronic diseases and the associated costs for their healthcare. Development and initial results of a hybrid plastic microfluidic device with an integrated graphene-protein biosensor chip for use in point-of-care (POC) is described. The initial prototype is a glucometer that uses optimized glucose oxidase bound to a graphene field effect sensor. Technologies required for development of the prototype include modification of the glucose oxidase for improved performance by protein engineering, methods to bind the enzyme to the graphene attached to the silicon oxide surface of sensor chip, and integration into a thermoplastic microfluidic device. Initial results indicate the prototype glucometer can measure glucose concentrations from low physiological levels to molar concentrations.